2015
DOI: 10.4236/ajps.2015.68113
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Micropropagation of a Valuable Medicinal Plant, <i>Plectranthus amboinicus</i>

Abstract: The effect of the plant growth regulators benzyl amino purine (BAP), 1-naphthaleneacetic acid (NAA) and kinetin (KIN) on in vitro shoot induction and proliferation of Plectranthus amboinicus was examined. Explants obtained from lateral shoots and apical shoots of P. amboinicus were inoculated on Murashige and Skoog (MS) culture medium supplemented with different concentrations of BAP, NAA and KIN. When the effect of each growth regulator was considered singly, the highest rate of shoot induction (80% of explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
(3 reference statements)
2
12
0
1
Order By: Relevance
“…MS basal media (1962) is the most commonly used plant culture media. As presented in Table 4, it has a very high salt content, nevertheless, it is the preferred medium for the growth of several species (Alvarenga et al 2015;Grzegorczyk-Karolak et al 2015;Rahman et al 2015). It has been demonstrated that different MS salt concentrations influence growth in several species (Assis et al 2012;Martins et al 2015;Shekhawat et al 2015;Singh et al 2015).…”
Section: Improvements In Traditional Culturing Techniquesmentioning
confidence: 99%
“…MS basal media (1962) is the most commonly used plant culture media. As presented in Table 4, it has a very high salt content, nevertheless, it is the preferred medium for the growth of several species (Alvarenga et al 2015;Grzegorczyk-Karolak et al 2015;Rahman et al 2015). It has been demonstrated that different MS salt concentrations influence growth in several species (Assis et al 2012;Martins et al 2015;Shekhawat et al 2015;Singh et al 2015).…”
Section: Improvements In Traditional Culturing Techniquesmentioning
confidence: 99%
“…e lack or slow shooting in PGR-free MS media is observed by many researchers in several Aloe species [15,19,21,22,[25][26][27][28][29]. e use of combination of auxins and cytokinins with MS media is known to be effective for optimal in vitro shoot proliferation in many species including aloes as compared to the use of either group of PGRs [11,25,30,31]. But establishing the best combinations and concentrations of auxins and cytokines for better shooting of explants is often tricky.…”
Section: Shooting Responsesmentioning
confidence: 99%
“…1i). The superiority of IBA over other auxins on in vitro rooting has been reported in Plectranthus ambonicus (Rhaman et al 2015) and Glinus lotoides (Teshome and Feyissa 2015). The number of roots per shoot was increased with increasing concentration of IBA from 0.1 to 1.0 mg/l, whereas subsequent concentrations decreased the frequency of rooting.…”
Section: Rooting Of Regenerated Shootsmentioning
confidence: 72%